A New Measure of Home Exercise Benefits and Barriers. Issue 2 (3rd March 2016) - Thind, Herpreet; Fava, Joseph; Traficante, Regina; Bock, Beth C.
Abstract : Background: To increase physical activity among college students, new approaches are needed including the exploration of home-based exercise. However, research related to potential facilitators and barriers to exercising at home is limited.Purpose: The goal of this study was to develop a reliable and valid measure that can assess predictors of home exercise.Methods: A systematic approach was used to develop items for the new measure and to examine its psychometric properties. Principal component analysis (PCA) was used to investigate the internal structure of the measure. External validity and initial construct validity were examined using correlations of the new subscale measures with existing valid measures of exercise.Results: Two hundred thirty-two adults (65% women and 72% white) completed a cross-sectional survey. The final PCA solution resulted in a 28-item measure with 7 distinct subscales with individual item loadings ranging from 0.64 to 0.91. These subscales comprised 3 higher order scales of Barriers to Home Exercise, Benefits of Home Exercise, and Barriers to Public Exercise. All demonstrated good internal consistency and external validity.Discussion: The measure developed in this study delineates important predictors of home exercise.Translation to Health Education Practice: This measure can be used to develop tailored interventions to promote home-based exercise.